Race, culture, psychology, & law - Barrett, Kimberly; George, William, 1954- (Sage Publications, 2005)
Race, Culture, Psychology, and Law is the only book to provide summaries and analyses of culturally competent psychological and social services encountered within the U.S. legal arena. The book is broad in scope and covers the knowledge and practice crucial in providing comprehensive services to ethnic, racial, and cultural minorities. Topics include the importance of race relations, psychological testing and evaluation, racial "profiling," disparities in death penalty conviction, immigration and domestic violence, asylum seekers, deportations and civil rights, juvenile justice, cross-cultu.